Interactions between sexually transmitted infections and human immunodeficiency virus in Southern Africa - Htun, Ye (My University, 2007)
Epidemiological information on sexually transmitted infections (STIs) is necessary to assess the magnitude of the burden of infections, to identify vulnerable population groups, to mobilise resources for intervention activities and to monitor the impact of these activities. In addition, specific STI surveillance systems, such as studies on the relative prevalence of aetiological agents of STI syndromes and their antimicrobial susceptibility patterns, are aimed at improving patient care. The studies included in this thesis were designed and implemented to improve our understanding of the epidemiology of STIs and HIV infection in southern Africa. In all the study populations, we observed that high level STI epidemics preceded the explosive spread of HIV infection among high-risk individuals. The studies reported here also demonstrate the importance of triangulating data collected from different recommended STI surveillance components, using a tiered surveillance approach. The studies reported here also explored the bidirectional interactions of HIV and STIs. We observed that different STIs have shown different magnitudes of interaction with HIV infection. We found particularly strong interactions between genital herpes and HIV. At the individual level, HIV-seropositive patients with genital herpes were more frequently found to have atypical clinical presentations, delays in spontaneous healing, longer duration of HSV shedding and increased association with HIV shedding from ulcer and genital exudates. Mixed infections involving chancroid and genital herpes were found to be common, particularly in HIV-seropositive patients. The effectiveness of syndromic treatment targeting only bacterial causes of genital ulceration was significantly reduced due to persistent ulcerations as a result of co-infection with genital herpes. The successful treatment of herpes in men and women was found to be associated with a decline or cessation in HIV shedding into ulcer exudates or genital fluid. The studies have also shown that HIV plasma viral load is the main determinant for HIV shedding in both men and women presenting with STIs. As was the case with HSV infection, there was a strong association between HIV and HPV infection in both men and women. A higher prevalence of HPV infection was found among HIV-seropositive patients in our study population and this may reflect the higher frequency of recurrences and/or longer duration of infection (i.e. persistency). The studies also found that the biological false positive reactions in syphilis serology (i.e. RPR) are not a common occurrence in our HIV-seropositive study population. On the other hand, syphilis serology could be falsely negative in patients with PCR-confirmed primary syphilis who are co-infected with HIV and other aetiological agents causing GUD. In conclusion, the findings of our studies have supported the bidirectional nature of interactions between conventional STIs and HIV infection in southern Africa.
Student Number : 9813645X - PhD thesis - Faculty of Health Sciences
Keywords: interactions; sexually transmitted infections; human immunodeficiency virus; Southern Africa